Erectile dysfunction: Is platelet-rich plasma the new frontier for treatment in patients with erectile dysfunction? A review of the existing evidence - Anastasiadis, Eleni; Ahmed, Razna; Khoja, Abbas Khizar; Yap, Tet (Frontiers in Reproductive Health, 2022)
Erectile dysfunction (ED) is one of the commonest disorders in adult males and affects 12-19% of men of reproductive age. Only few studies have evaluated the impact of ED on men and couples with infertility - these studies report higher rates of ED in this sub-group of men compared to the general population, with the prevalence of ED in men diagnosed with male infertility ranging from 6.7-61.6%. Nevertheless, ED is considered a rare cause of male infertility, accounting for about 0.4-5% of all causes of male infertility. ED remains a poorly treated condition globally and current therapies, like oral medication, offer only temporary symptomatic relief and do not influence disease progression - patients are potentially on lifelong treatment, with ED worsening over time. In contrast, regenerative medicine may potentially reverse or halt the progression of ED processes. In this article, we review the evidence for intracavernosal injections of platelet-rich plasma (PRP) in the treatment of ED.